Amanita minqingensis, a novel taxon of Amanita section Vaginatae (Amanitaceae, Agaricales) from Southern China - Guan, Xiayu; Zhu, Mengjia; Keyhani, Nemat O; Dang, Yuxiao; Lv, Huajun; Wu, Ziyi; Heng, Zhiang; Chen, Ruiya; Liu, Sen; Lai, Pengyu; Yang, Chenjie; Chen, Jinhui; et al. (Phytotaxa, 2024)
A new species of Amanita, A. minqingensis, is described from Fujian province, China, based on morphological and multi-phylogenetic sequencing including the nuclear ribosomal large subunit (nrLSU), nuclear ribosomal internal transcribed spacer (ITS), RNA polymerase large subunit-2 (rpb2), and translation elongation factor-α (tef1-α) loci. We identify the species as a member in Amanita section Vaginatae, subg. Amanita. The new species is characterized by its tan pileus with putty verrucose volval remnants, the absence of clamps and globose to sub-globose basidiospores ((9‒)9.2‒10.3‒11 × (8.5‒)9‒9.5‒10.5). Detailed descriptions, color photographs of fresh basidiomata, line drawing of microscopic characters and a phylogenetic tree based on ITS sequence data are are provided.